Research of pulse position based on gradient pressure method. (February 2023) - Bi, Ruiyu; Zhao, Yunlong; Ma, Yuhang; Zhu, Xiaolong; Li, Jiawei; Wu, Bin; Zang, Junbin; Men, Jiuzhang; Zhang, Zhidong; Xue, Chenyang
Highlights: The pulse signal detection probe combined with MEMS pressure sensor and human muscle impedance matching medium is used to realize flexible coupling. The gradient pressure method is used to detect the pulse signal, which is different from the previous three parts of floating, sinking and getting a more complete pulse signal. The slope index is proposed to describe the variation law of pulse signal with the change of applied pressure, the square difference index is proposed to determine the flat pulse threshold, and the digital standard of pulse position is defined. the feasibility of defining pulse position by using single diabetes case and TCM syndrome type. Abstract: Pulse position is an important part of pulse diagnosis of traditional Chinese medicine. The standardization of pulse position is the key to the digitization of pulse diagnosis. A pulse wave detection method and pulse position determination method based on gradient pressure are presented. The relationship between the depth of radial artery and the best pulse-taking pressure is discussed by Doppler ultrasonic detection of radial artery.And the difference between the best pulse-taking pressure and pulse position is pointed out. The criteria for defining pulse position by slope index and square difference index are proposed and calculation method is given. The pulse wave of 4 diabetic patients was measured and slope index and square difference index were calculated. The results were in line with the clinical diagnosis of traditional Chinese medicine, and the feasibility and accuracy of pulse position definition were verified. It provides a way of thinking for the digitization of pulse diagnosis in the future.